2011
DOI: 10.1002/clen.201000100
|View full text |Cite
|
Sign up to set email alerts
|

Application of Agro‐Based Biomasses for Zinc Removal from Wastewater – A Review

Abstract: Zinc remediation of aqueous streams is of special concern due to its highly toxic and persistent nature. Conventional treatment technologies for the removal of zinc are not economical and further generate huge quantity of toxic chemical sludge. Biosorption is emerging as a potential alternative to the existing conventional technologies for the removal of metal ions from aqueous solutions. Mechanisms involved in the biosorption process include chemisorption, complexation, adsorption-complexation on surface and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 99 publications
0
28
0
1
Order By: Relevance
“…Working solutions of concentrations 1,5,10,15,20,25,30,40, 50 ppm were prepared by using appropriate amount of stock cadmium solution.…”
Section: Preparation Of the Stock Solution Of Cadmium Nitratementioning
confidence: 99%
See 1 more Smart Citation
“…Working solutions of concentrations 1,5,10,15,20,25,30,40, 50 ppm were prepared by using appropriate amount of stock cadmium solution.…”
Section: Preparation Of the Stock Solution Of Cadmium Nitratementioning
confidence: 99%
“…These functional groups bind metal through ion exchange by transferring hydrogen ions or through complex formation by sharing electron pair [15]. Most of these agricultural materials showed significant adsorption capacities than Granular Activated Carbon [13].…”
mentioning
confidence: 99%
“…10, addition of NaCl to the material is expected to result in weakening of the complex such that the salt ions behave as counter-ions to the charged polyelectrolyte chains. The effectiveness of the PEC-type hydrogels to enable the removal of NaCl from solution is notable because most reported applications of cellulosic-based materials for ion exchange have involved removal of divalent metal ions (Rudie et al 2006;Hubbe et al 2011;Kumar et al 2011). In such applications it is typical for the divalent ions to displace monovalent ions within the substrate due to their greater binding constants.…”
Section: Counterionmentioning
confidence: 99%
“…It is reported that the use of untreated biomass as the biosorbent can lead to high chemical oxygen demand (COD) due to the release of soluble organic compounds contained in these materials. Also these materials discharge color in the treated water 17 . We found that Grewia asiatica fruit seed did not release any color into the system at any pH (acidic, neutral or basic), hence can be used without any treatment.…”
Section: Sorbent: Grewia Asiatica Fruit Seedmentioning
confidence: 99%